The Great Irish Famine in Irish and UK history textbooks, 2010–2020. Issue 1 (13th April 2023) - Janssen, Lindsay
Abstract : This article considers the representation of the controversial issue of the Great Irish Famine (1845–50) in 27 recent Irish and UK history textbooks for the secondary level. Key contested issues – imports and exports, the British government's laissez-faire economic policy, providentialist interpretations, and victim–perpetrator discourses – have long formed part of the narrative repertoire of Famine history; their representation and narrativisation in textbooks is analysed through narrative and content analysis. Historical contextualisation and perspective taking are considered key skills for students studying history; these skills become even more important when dealing with controversial issues. The questions central to this research are: How do secondary-level history textbooks from Ireland and the UK represent the key contested elements regarding the Famine? Do they provide sufficiently complex accounts, thereby facilitating historical contextualisation and perspective taking? While some Irish and UK textbooks offer learners complex representations of the Famine, several others provide students with insufficient opportunity for perspective taking, and for developing a thorough understanding of the historical context. Specifically, the majority of the textbooks provide simplistic victim–perpetrator discourses. As such issues complicate historical contextualisation, perspective taking and, relatedly, empathy formation, the article suggests including more complex subject positions in textbook discussions of the Famine.